Analisis Pengembangan UMKM Melalui Digital Entrepreneurship dengan Model Triplehelix pada Pasar Hanggar Talasalapang di Kota Makassar - Aryuniasari; Rakib, Muhammad; Ahmad, M. Ihsan Said; Mustari (Journal of Economic Education and Entrepreneurship Studies, 2023)
This research aims to find out how the development of MSMEs through digital entrepreneurship at the Talasalapang Hangar Market in Makassar City. This research is categorized as descriptive qualitative research. In this research, key informants were used to collect data through observation, interviews, and notes, then analyzed using data reduction, data presentation, and conclusion drawing. The results of this study were obtained from these indicators, namely academic support, businesspeople and government in Triplehelix which are supporting factors and inhibiting factors for MSME actors.